2020
DOI: 10.17159/2078-516x/2020/v32i1a7596
|View full text |Cite
|
Sign up to set email alerts
|

Brace yourselves: esports is coming

Abstract: Background: Competitive gaming (or esports) is an emerging phenomenon with a field of over 454 million fans globally. Despite its tremendous popularity and commercial support, esports is not widely understood. It is also disregarded as a reputable or credible form of competition. The International Olympic Committee (IOC) contends that esports may be considered a sporting activity, but this is limited to the basis of its sedentary nature and poor governance. Discussion: These a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…It is, therefore, arguable whether this extends to gamers engaged with high-intensity gaming, such as esports athletes. Indeed, these gamers may not match the levels of physical exertion experienced by traditional athletes; however, the level of intensity may be comparable to the cognitive effort (or "mental fitness") required to maintain their proficiency and competitive status (Kemp et al, 2020). While this is speculative, it is likely that novel performance metrics, such as actions per minute (APM), which measure game input commands, could be used as an objective proxy for gaming intensity in the future (Bonnar et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is, therefore, arguable whether this extends to gamers engaged with high-intensity gaming, such as esports athletes. Indeed, these gamers may not match the levels of physical exertion experienced by traditional athletes; however, the level of intensity may be comparable to the cognitive effort (or "mental fitness") required to maintain their proficiency and competitive status (Kemp et al, 2020). While this is speculative, it is likely that novel performance metrics, such as actions per minute (APM), which measure game input commands, could be used as an objective proxy for gaming intensity in the future (Bonnar et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that esports will have a total audience of 646 million people and global revenue of $1.6 billion by the end of 2023 (Newzoo, 2020). There are also schools of thought dedicated to extending health and performance research and optimizing the performance of esports athletes (Bonnar et al, 2019;Kemp et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…3 Competitive gaming, known as eSports, is a billion dollar enterprise with a growth rate of 14% each year and has an estimated fan base of 454 million fans across the world. 4 A study conducted across several countries including the USA and UK, found that the mobile phone was the most popular device to game on, followed by the computer (laptop or desktop) and gaming consoles (Xbox, Playstation, etc), with the least popular being the Tablet. 5…”
Section: Introductionmentioning
confidence: 99%
“…[1] The paper "Physical and physiological profile of U18, U19, U21 and senior elite netball players" [2] had 514 downloads and the paper "Brace yourselves: esports is coming" was the third most popular paper with 424 downloads. [3] The broad interest in physical activity and sport and Covid-19 was not neglected. Two commentaries on Covid-19, two position statements compiled by the South African Sports Medicine Association and one short report on the wearing of face masks during exercise were published.…”
mentioning
confidence: 99%